2005
DOI: 10.1016/j.physrep.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Driven quantum transport on the nanoscale

Abstract: We explore the prospects to control by use of time-dependent fields quantum transport phenomena in nanoscale systems. In particular, we study for driven conductors the electron current and its noise properties. We review recent corresponding theoretical descriptions which are based on Floquet theory. Alternative approaches, as well as various limiting approximation schemes are investigated and compared. The general theory is subsequently applied to different representative nanoscale devices, like the non-adiab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
922
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(937 citation statements)
references
References 209 publications
(458 reference statements)
13
922
1
1
Order By: Relevance
“…[19][20][21] ). When the original Hamiltonian of the two band system is given by a Bloch Hamiltonian H orig (k), the time dependent Hamiltonian of the system driven by E(t) = Ee −iωt + E * e iωt is given by…”
Section: Nonlinear Optical Effects and Floquet Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] ). When the original Hamiltonian of the two band system is given by a Bloch Hamiltonian H orig (k), the time dependent Hamiltonian of the system driven by E(t) = Ee −iωt + E * e iωt is given by…”
Section: Nonlinear Optical Effects and Floquet Approachmentioning
confidence: 99%
“…Now we study dc current in the x-direction induced by circularly polarized light for the steady state described by the Floquet state in Eq. (20). The velocity operator in the x-direction is written up to linear order in A aŝ…”
Section: Nonlinear Optical Effects and Floquet Approachmentioning
confidence: 99%
“…It has been found that the irradiation of a periodically oscillating THz wave causes photon-mediated tunneling in quantum wells (QWs), superlattices (SLs), and Wannier-Stark ladders (WSLs). In particular, the application of an appropriately controlled periodic drive to these systems brings quantum transport and diffusion to an almost complete stop [5]. In THz-driven SLs and WSLs, the latter of which are also called as dynamic WSLs (DWSLs), such spatial localization, called as dynamic localization (DL), is characterized by the collapse of quasienergy minibands [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, such a transmission can also be considered as an elastic tunneling process [5,12,13]. Recent extensions of the Landauer theory also include inelastic tunneling processes [14,15]. An approximate effective Landauer approach that accounts for inelastic phonon processes has been studied in Refs.…”
Section: Introductionmentioning
confidence: 99%